Purification and characterization of anti-multidrug resistances bacteria from actinomycetes associated sponge - Herlina Rante; Wahyono .; Yosi B. Murti; Gemini Alam (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Actinomycetes are one kind of the microorganisms that very important producer of secondary metabolites for drugs.Active substances of microbial origin have been searched through a series of screening methos to obtain novel compounds and strains. The purpose of this research was to characterize the antibacterial coumpound from actinomycetes associated sponge and identification of actinomycetes base on morfology and fisiology characteristic. Isolation of actinomycetes from sponge were done bypour and spreap plate. A total of actinomycetes strain were isolated from sponges collected at Barrang Lompo island, Makassar, South Sulawesi, Indonesia. One of them showed strong activity against antibiotic resistant bacteria with concentration 0.0195µg. Characterisation of antimicrobial coumpound base on IR spectrum determined derivate of carboxylic acid. The result obtained from the morphological and physiological characterisation, determined the strain a Streptomyces spKey words: sponges, actinomycetes, secondary metabolic, bacteria resistan